Design of a Web-Based Digital Archive Information System for Incoming and Outgoing Mail Case Study of the Rambang Kapak Tengah District Office - Sagita Vira; Suhartini; Iwan Setiawan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Well-organized archives are an important element in supporting smooth operations and public services in government agencies. The Rambang Kapak Tengah Subdistrict Office still uses manual methods in managing records. This is often inefficient and susceptible to damage and data loss. This research aims to design a web-based digital archive information system that is able to increase efficiency and reliability in managing archives in the office. The method used is the RAD development model which includes requirements analysis, design, implementation and testing stages. The resulting system makes it easy to store, search and manage archives digitally. This helps minimize the risk of data loss and improves ease of access and security of information. It is hoped that the implementation of this system can support more effective and efficient archive management at the Tanjung Rambang village sub-district office.